AB0290 Lower educational levels are associated with a higher risk of rheumatoid arthritis in a southern european nested case-control study. (12th June 2018) - de Pablo, P.; Romaguera, D.; Panico, S.; Mattiello, A.; Gavrila, D.; Navarro, C.; Sacerdote, C.; Vineis, P.; Tumino, R.; Ollier, W.; Riboli, E.; Venables, P.; et al.
Abstract : Objectives: To investigate the association between socioeconomic status (SES) on an individual level and incident RA Methods: EPIC is a multicentre, pan-European prospective cohort study of apparently healthy populations. We undertook a nested case-control study to investigate risk factors for RA, by identifying incident RA cases (pre-RA) and matched controls amongst subjects enrolled in four EPIC cohorts in Italy and Spain. The lifestyle, environmental exposure, anthropometric information and blood samples were collected at baseline. Confirmed pre-RA cases were matched with controls by age, sex, centre, and date, time and fasting status at blood collection. The exposure was SES as measured by level of educational attainment categorised as university (referent), secondary school/technical/professional school, primary school completed, and none. The primary outcome was incident RA. Conditional logistic regression (CLR) analysis was adjusted for ACPA seropositivity, smoking status, and presence of shared epitope (SE). A further model also adjusted for other potential confounders, including body mass index (BMI), waist circumference, physical activity, and alcohol intake. Results: The study sample included 398 individuals of which 99 individuals went on to subsequently develop RA. In this analysis, time to diagnosis (defined as time between date of blood sample and date of diagnosis), was 6.71 years (SD 3.43). A significant positive association was observed with level of educational attainment and RA incidence (secondary/technical vs university: OR 5.60, 95% CI 1.59–19.7, primary school vs university: OR 5.06, 95% CI 1.45–17.6, no education vs university: 7.11, 95% CI 1.37–36.8; p for trend 0.02) independent of ACPA seropositivity, SE and smoking). A significant positive association between level of educational attainment and RA incidence was confirmed in the fully adjusted model (secondary/technical vs university: OR 5.52, 95% CI 1.53–19.9, primary school vs university: OR 4.87, 95% CI 1.38–17.1, no education vs university: OR 6.48, 95% CI 1.21–34.6; p for trend 0.02). Conclusions: Lower educational levels were independently associated with higher risk of incident RA in this European Mediterranean population. Disclosure of Interest: None declared